2022
DOI: 10.1007/s40614-022-00338-x
|View full text |Cite
|
Sign up to set email alerts
|

Applied Behavior Analysis in Children and Youth with Autism Spectrum Disorders: A Scoping Review

Abstract: This manuscript provides a comprehensive overview of the impact of applied behavior analysis (ABA) on children and youth with autism spectrum disorders (ASD). Seven online databases and identified systematic reviews were searched for published, peer-reviewed, English-language studies examining the impact of ABA on health outcomes. Measured outcomes were classified into eight categories: cognitive, language, social/communication, problem behavior, adaptive behavior, emotional, autism symptoms, and quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 139 publications
0
18
0
1
Order By: Relevance
“…METODO RESULTADOS DISCUSIÓN REFERENCIAS 2020;Yu et al, 2020;Raches et al, 2019;Reichow et al, 2018;Makrigianni et al, 2018;Gitimoghaddam et al, 2022;Fernández-Menéndez et al, 2022), sin embargo, es escasa la literatura que engloba las estrategias conductuales que se utilizan hoy en la atención de las personas con TEA. Por tanto, el objetivo de este estudio es realizar una revisión sistemática de las estrategias de intervención conductual, basadas en la evidencia hallada en niños y niñas con diagnóstico de TEA en edad escolar, entendiendo las intervenciones conductuales como la aplicación sistemática de los principios y técnicas conductuales con el fin de evaluar y modificar comportamientos, propiciando así un funcionamiento oportuno (Martin & Pear, 2008).…”
Section: Iniciounclassified
“…METODO RESULTADOS DISCUSIÓN REFERENCIAS 2020;Yu et al, 2020;Raches et al, 2019;Reichow et al, 2018;Makrigianni et al, 2018;Gitimoghaddam et al, 2022;Fernández-Menéndez et al, 2022), sin embargo, es escasa la literatura que engloba las estrategias conductuales que se utilizan hoy en la atención de las personas con TEA. Por tanto, el objetivo de este estudio es realizar una revisión sistemática de las estrategias de intervención conductual, basadas en la evidencia hallada en niños y niñas con diagnóstico de TEA en edad escolar, entendiendo las intervenciones conductuales como la aplicación sistemática de los principios y técnicas conductuales con el fin de evaluar y modificar comportamientos, propiciando así un funcionamiento oportuno (Martin & Pear, 2008).…”
Section: Iniciounclassified
“…During the past 60 years, ABA has changed considerably, evolving into many treatment practices, with the aim of dealing with the problems of individuals with ASD in all functioning domains, such as cognition, social skills, language, daily living skills, and challenging behaviors. 42 Today, only a small minority of these subjects come off the autistic spectrum, but almost all can improve considerably by increasing their level of autonomy. 43 After the diagnosis, psychoeducational and often emotional support are very important for parents.…”
Section: Treatments For Autism and Longterm Outcomementioning
confidence: 99%
“…Gitimoghaddam et al [ 7 ] searched seven online databases and identified systematic reviews for published peer-reviewed English-language studies examining the impact of ABA on health outcomes. They classified measured ABA outcomes into eight categories: cognitive, language, social/communication, problem behavior, adaptive behavior, emotional, autism symptoms, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Applied behavior analysis has been extensively recognized as the gold standard for treating ASD. This acknowledgment comes from decades of research and a large body of supporting evidence [ 7 ]. Applied behavior analysis is popular and widely preferred.…”
Section: Introductionmentioning
confidence: 99%